Practical Teaching Methods for Electronic in Vocational Colleges Used by Teachers - Nasir, Ahmad Nabil Md; Ahmad, Adnan; Udin, Amirmudin; Abd Wahid, Nur Husna; Ali, Dayana Farzeeha (Journal of Technical Education and Training, 2020)
There are many challenges faced by teachers to ensure that every student is able to master the knowledge which is in line with the industry. Hence, the practical teaching approach that is used by teachers needs to be in line with the syllabus that is being constructed. Teachers are seen to be important characters in order to ensure that each student can master the contents of the lessons in the classroom well. The objective of this study is to investigate the practical methods of teaching electronic subject at Vocational Colleges which is often used by teachers in conducting the practical workshop. Quantitative studies were employed using questionnaires and the respondents of this research were 135 electronic teachers in 58 Vocational Colleges which offer Electrical and Electronics Engineering Technology courses. Descriptive analysis was used in this study and the data such as mean, standard deviation and ranking were analysed. The results showed that the Electronics teachers used several methods in delivering the electronic practical subjects which are in line with the industry nowadays. Based on this study, teachers used several practical teaching methods in class in order to ensure that every student will understand and they can use it when they become professional workers in specific electronics industry.